Caracterização da superfície usinada por fresamento de faceamento por meio da rugosidade ao longo da vida da ferramenta - Eurich, Alexandre Maier (2021)
The surface finish is generated, among other factors, by printing the profile of the cutting edge of the tool on the part being machined. Cutting edges in original conditions (which did not wear) tend to generate regular machined surfaces, with a better surface finish. However, as the tool suffer wear, its edge starts to present irregular geometries and, these irregularities, start to be printed on the surface of the part. Many researchers have developed researches that evaluates the surface finish of the machined material for different machining conditions and different cutting tools, however there are still some issues little explored, mainly in terms of: monitoring, periodically, the geometric changes in the cutting tools because of the wear; evaluate, besides the medium roughness, other roughness parameters that present a behavior as the tool wears and; search relationships, even if qualitatively, between the behavior of the roughness parameters and the geometric changes of the cutting edge. In view of this, the present research aims to evaluate the roughness behavior of milled surfaces as the secondary cutting edge of the tool changes its original geometry due to wear. The face milling experiments were carried out on ABNT 1045 steel blocks, for some machining conditions and using two similar cutting tools (both carbide and ISO P40), but from different manufacturers. Roughness data were obtained by means of an optical profilometer (which also allowed evaluations of the topography of the machined surface) and the wear inspected by a scanning electron microscope (SEM). The maximum flank wear of the secondary cutting edge, measured periodically in the SEM analysis, was used to determine the life of the cutting tools for each machining condition. Was made the monitoring of the secondary cutting edge to accompany its geometric change because it is the edge that generates the machined surface. When there was adhesion at the cutting edge, were observed more pronounced valleys, reduced peaks with wider ridges and negative skewness in the topography of the piece. The tool with a higher wedge angle, besides to having a longer life time, showed less changes in the behavior of the roughness parameters. Both tools failed due the wear of notch that evolved from thermal cracks and not because they reached the predetermined value of maximum flank wear (200 μm).